2015
DOI: 10.1002/ldr.2451
|View full text |Cite
|
Sign up to set email alerts
|

Are There Arid Land Soilscapes in Southwestern Europe?

Abstract: No studies have proven the existence of soil assemblages typical of arid lands in Europe. This study was carried out in a representative territory of the southeastern part of the Iberian Peninsula, Almería province, which is the driest part of Europe, to determine if soils characteristic of arid lands are present. In order to analyse the spatial distribution of soils, the authors made use of mathematical tools previously developed in biodiversity and pedodiversity analysis, such as richness, entropy indices, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Khaledian et al Catena 158 (2017) 194-200 soils have been ploughed for millennia, leading to soil erosion and degradation (Ibáñez et al, 2015). The results for the pasture categories and for the USA and Iraq were consistent with previous studies.…”
Section: Discussionsupporting
confidence: 85%
“…Khaledian et al Catena 158 (2017) 194-200 soils have been ploughed for millennia, leading to soil erosion and degradation (Ibáñez et al, 2015). The results for the pasture categories and for the USA and Iraq were consistent with previous studies.…”
Section: Discussionsupporting
confidence: 85%
“…Spatial heterogeneity has been reported in urban soils (Howard & Orlicki, ; Ibáñez et al, ; Howard & Orlicki, ). Spatially significant variations were apparent in this study as indicated by CA, showing remarkable spatial heterogeneity in the urban soils due to anthropogenic activities such as urbanization and home construction around the Zirata village (Tajgardan et al, ; Khaledian et al, ).…”
Section: Discussionmentioning
confidence: 77%
“…The soil subgroup is an intergrade between Lithic and Typic Rhodoxeralfs (García del Barrio et al, 1971;Soil Survey Staff, 1999), with a loamy sand texture and a maximum depth of 1.2 m to the calcarenite bedrock. In areas with weakly developed soils, such as the Setenil region, the rugged relief often leads to partial loss of the topsoil layer (Ibañez et al, 2015;Symeonakis et al, 2014). This is a natural process aggravated by certain agricultural practices (eg tillage) (Gómez et al, 2009;Keesstra et al, 2016;Taguas and Gómez, 2015;Vanwalleghem et al, 2011), leading to outcropping of the bedrock and to the appearance of localised zones where the humus-rich horizon rarely exceeds 0.1 m. The climate is Mediterranean, with a mean annual precipitation of 700 mm, where 75% of the rainfall occurs from October to May.…”
Section: Methodsmentioning
confidence: 99%